Top Serving Ability in BKMF Sparta FIKK UNM Volleyball Games - Juhanis; Nurulita, Retno Farhana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to determine BKMF Sparta FIKK UNM athletes' volleyball serviceability. This type of research is known as descriptive research. The research sample comprised 20 athletes, selected through a sampling technique from the entire population of athletes participating in the BKMF Sparta FIKK UNM, for 20 participants. This study utilizes a volleyball serviceability test. We used descriptive statistics for data analysis, ensuring a 95% truth level. The research results from the UsinprogrammeS version 25.00 program revealed that out of 20 athletes, or 100%, BKMF Sparta FIKK UNM athletes had the best serving ability in volleyball; 1 athlete, or 5.0%, falls into the excellent category, and 3 athletes, or 15.0%, belong to the good group. The moderate category included 10 athletes (50.0%), the poor category included 5 athletes (25.0%), and the very poor category included 1 athlete (5.0%). Therefore, it can be said that the best serving ability of BKMF Sparta FIKK UNM athletes in volleyball is in the medium group if you look at the final statistical percentage.